Solomon Islands : 2011 Article IV Consultation, Third Review Under the Stand-by Credit Facility, and Request for Arrangement Under the Stand-by Credit Facility: Staff Report; Staff Supplements; Public Information Notice and Press Releases; and Statement by the Executive Director for Solomon Islands. (IMF Staff Country Reports; Country Report, 2011)
Solomon Islands' economy has rebounded from the 2008-09 global financial crisis. An 18-month Standby Credit Facility has been approved in June 2010 and succeeded in restoring macroeconomic and financial stability. A new resource taxation regime is the key to reap the benefits from natural resource wealth and ensure that the government receives a fair share of mining revenue. Reforms of mining legislation should be a key part of a broader set of measures to improve the investment climate and the regulatory framework.